Modeling an aspirational connected network of protected areas across North America - Barnett, Kevin; Belote, R. Travis (Ecological applications, 2021)
Connecting protected areas remains an important global conservation strategy in the face of ongoing and future threats to biodiversity. Amid our growing understanding of how species’ distributions will respond to climate change, conservation scientists need to plan for connectivity conservation across entire continents. We modeled multiscale connectivity priorities based on the least human‐modified lands between large protected areas of North America using least‐cost and circuit theory approaches. We first identified priority corridors between large protected areas, then characterized the network’s structure to unveil priority linkages most important for maintaining network‐ and regional‐level connectivity. Agreement between least‐cost corridors and current flow varied throughout North America, reflecting permeable landscape conditions and “pinch points” where potential ecological flows may concentrate between protected areas. Priority network‐level linkages derived from each approach were similar throughout the continental network (e.g., Rocky Mountains and Canadian boreal), but critical linkages that bridged regional protected‐area networks varied. We emphasize the importance of planning for connectivity at continental scales and demonstrate the utility of multiple methods when mapping connectivity priorities across large spatial extents with wide gradients in landscape conditions.